Mobilizing COVID-19 Testing: Impact and Challenges. (28th October 2021) - Odenbrett, R; Ingemansen, D; Baumgart, T; Hieb, V; Ross, A; McDowell, J; Chang, R; Strouts, F
Abstract: Introduction/Objective: In response to the rapidly evolving COVID-19 pandemic, Sanford Health developed a mobile diagnostic testing program capable of reaching geographically dispersed sites and communities. These mobile laboratories provided on-site testing and sensitive detection of SARS-CoV-2 by leveraging Cepheid's GeneXpert platform, enabling rapid reporting of results directly to the patient and physician. Aggregation of these results allowed monitoring population infection rates and public health reporting. Methods/Case Report: Within 3 weeks of conception, the first mobile unit was designed, engineered and deployed. Key requirements for successful implementation included mobile lab licensure, CLIA certification, COLA enrollment, Quality and Risk assessments, inventory management, lab maintenance and ongoing monitoring. Testing was performed using the Xpert Xpress SARS-CoV-2 test and the population tested were primarily asymptomatic individuals. Results (if a Case Study enter NA): Between May 3rd, 2020 and June 23rd, 2021, a total of 31, 148 Xpert Xpress SARS-CoV-2 tests were run across 3 mobile laboratories, with an average of 600 tests performed per week. The percent positivity ranged from 0% to 5.8%, reaching highest positivity in week beginning May 10th, 2020. The average turnaround time from sample collection to result verification was 2.0 hours, and the average time from sample receipt to result verification was under 1 hour. Conclusion: Sanford Health's mobile testing program brings SARS-CoV-2 PCR testing to the community and dramatically reduces the time from sample collection to result reporting compared with traditional testing labs, enabling rapid intervention following a positive result. The flexibility of the GeneXpert platform, including the instrument's robustness, the independently functioning analyzers, and the wide range of tests available, makes it particularly well suited to mobile laboratories. This program demonstrates the impact of on-site testing and highlights the challenges that were overcome for successful implementation, providing a blueprint to support the development of other mobile laboratories in the US.